Wpływ cech systemu bankowego w Polsce na transmisję polityki monetarnej - Piotrowska, Maria (The Impact of Financial Characteristics on the Monetary Policy Transmission in Poland, 2006)
The purpose of the paper is to determine the relevance of financial characteristics connected with the bank behaviour to the efficiency of loosening monetary policy. The following factors are examined: the level of concentration in banking system, bank health, sources of loan funds and a buffer stock of securities. The obstacles in transmitting the changes in monetary policy to a real economy, revealed in the paper, suggest that in Poland loosening monetary policy cannot be considered a powerful tool in mitigating unemployment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1138, s. 17-27